Relevansi Theologi Rasionalis Islam dan Nilai Kejuangan Jemaat Ahmadiyah Indonesia Dalam Mempertahankan Eksistensinya - Catur Wahyudi (Publisia: Jurnal Ilmu Administrasi Publik, 2016)
This article reveal the relevance of Islamic rationalist theological stream with struggle value of Ahmadiyya in Indonesia (JAI). Through this analysis will be explained motif of JAI action in response to the pressures experienced. Some of the conclusions in this study it appears that the theological approach of the Ahmadiyya Community has also relevant to groups that collaborate flow streams that have been there - Asy'ariyah and Mu'tazilah - and ideological can be inserted into the flow rationalist Islamic theology. Significant indications can be explained by the standard norms of the personality of Ahmadi, as well as the teachings of Mirza Ghulam Ahmad, who embraced the Ahmadi, as recorded in "Kisyti Nuh". The whole motive of action in response to pressure and intolerance are oriented in an effort to maintain its existence, as far as possible avoid / minimize of conflicts and prioritizing of peace.DOI: https://doi.org/10.26905/pjiap.v1i2.442